Influência da altura das armadilhas Escolitídeo/Curitiba e Marques/Carrano na captura de Scolytidae (Insecta: Coleoptera) em floresta primária da Amazônia Central. - Abreu, Raimunda Liege Souza d (Instituto Nacional de Pesquisas da Amazônia - INPA, 1995)
A survey on the occurrence of insects of the Scolytidae family (Coleoptera) was carried out in the area of primary forest o£ the Forest Reserve Adolpho Ducke, with flight traps Escolitídeo/Curitiba and Marques/Carrano, installed at heights of 1, 3, 5, 7.5 and 10m. The collected data were evaluated quantitatively and qualitatively. For the more frequent species, statistical analysis were conducted to verify the frequency of occurrence at the tested heights, flight heights preference, and efficiency o£ the insect traps. The influente of climatic factors in the capture of insects was also verified. From the 7.974 Scolytidae insects collected, 4.131 (51.81%) were captured in the Escolitídeo/Curitiba traps and 3.843 (48.19%) in the Marques/Carrano traps. The genus Xyleboruswas responsible for more than 50% of the total collection and the species Xyleborus affinis Eichhoff, 1867, was predominant during the whole period of the experiment. The species X. affinis, Xyleborus spl and Monarthrum spl had preference for heights below 5m; Premnobius cavipennis Eichhof f , 1878, preferred heights above 3m; Cryptocarenus heveae (Hagedorn), 1912, above 5m; C. diadematus Eggers, 1937, above 7.5m; the species Hypothenemus erudi tus Westwood, 1836, H. obscurus (Fabricius), 1801, and Xylosandrus compactus Eichhoff, 1868, presented discrepancy concerning flight preference, considering the flight traps utilized in these experiments. The two insect traps used in this work did not present significant differences in efficiency, despite the slight numeric superiority of the insects collected in the trap Escolitídeo/Curitiba. Specific analysis has shown that the trap Escolitídeo/Curitiba was more efficient in capturing X. a f f i n i s and Xyleborus spl at lm above the ground and C. heveae at 5m. The trap Marques/Carrano has captured more H. eruditus at 10 m and C. heveae at 7.5m. It was also observed that climatic factors may affect the flight behaviour of the species X. a f f i n i s , P. cavipenis, X. compactus e Xyleborus spl and probably do not affect the flight behaviour of the species Monarthrum spl, H. eruditus, H. obscurus, C. diadematus and C. heveae.
Keywords: Floresta primária; Scolytidae